Internationalization: A Decade of Changes and Challenges - Knight, Jane (International Higher Education, 2008)
During the last decade internationalization has increased in importance, impact, and complexity. In fact, international education is now seen by both politicians and academic leaders as instrumental to regionalization initiatives. students. In the past decade the importance and benefits of internationalization have been recognized, but at the same time, new risks have been widely acknowledged, such as commercialization, foreign degree mills, brain drain, and growing elitism. All in all, we have seen a very dynamic evolution of internationalization in the past 10 years.